Characteristics, origin and significance of chessboard subgrain boundaries in the WAIS divide ice core - Joan J. Fitzpatrick; Larry A. Wilen; Donald E. Voigt; Richard B. Alley; John M. Fegyveresi (Annals of Glaciology)
Observation of thin sections of the WAIS (West Antarctic Ice Sheet) Divide ice core in cross-polarized light reveals a wealth of microstructures and textural characteristics indicative of strain and recovery in an anisotropic crystalline substance undergoing high-temperature plastic deformation. The appearance of abundant subgrain domains—relatively strain-free regions inside crystals (grains) surrounded by walls of dislocations across which small structural orientation changes occur—is particularly noticeable in the depth range associated with the brittle ice (∼650–1300 m). Here we describe a subgrain texture, not previously reported in ice, that resembles chessboard-pattern subgrains in β-quartz. This chessboard texture at WAIS Divide is strongly associated with the presence of bubbles. We hypothesize that chessboard-subgrain development may affect grain-size evolution, the fracture of ice cores recovered from the brittle ice zone and perhaps grain-boundary sliding as well.